الجوانب القانونية لأزمة سد النهضة في ضوء مبادئ القانون الدولي العام - العزازي، نبيل محمد خليل إبراهيم (الجمعية المصرية للاقتصاد السياسي والإحصاء والتشريع, 2021)
Renaissance Dam imposed itself on the international scene, when Egypt introduced a proposal taking into consideration Ethiopia’s needs for electricity from the dam, without harming Egyptian water interests. Ethiopia’s unilateral policy for construction of the Dam without prior notification to Egypt and Sudan, was a violation to Nile Basin agreements and international norms., so an effective international role is required to reach a balanced agreement respecting the international law governing International rivers.
Keywords: القانون الدولي -- أزمة سد النهضة -- المصالح المائية المصرية -- الموارد المائية -- إثيوبيا